Using Adaptive Interaction to Simplify Caregiver’s Communication with People with Dementia Who Cannot Speak - Astell, Arlene J.; Shoaran, Sarah; Ellis, Maggie P. (Frontiers in Communication, 2022)
Caregivers find it difficult to interact with people with dementia who have lost the capacity for speech. Adaptive Interaction is a simplified approach that uses the nonverbal fundamentals of communication to connect with people who can no longer speak. This study develops and tests Adaptive Interaction as a method for equipping caregivers with these nonverbal skills to increase communication with the people they care for. Six caregivers were each paired with one individual with dementia and trained in Adaptive Interaction. After receiving training in Adaptive Interaction, caregivers identified more communicative behaviours in their interactions partners and engaged in more frequent positive social behaviours and meaningful actions during interactions. These findings suggest that it is possible to equip staff to use simplified communication based on nonverbal fundamentals to connect with people with dementia who can no longer speak.